"Hot Seat" Simulation Model for Conflict Resolution: A Pilot Study. Issue 4 (July 2018) - Kim, Sara; Frans, Elise; Bohannon, Isaac; Barr, Karen; Buttrick, Elizabeth; Fehr, Ryan; Shannon, Sarah E.
Abstract : Background: Unresolved conflicts in health care threaten both clinician morale and quality of patient care. We piloted a training model that targeted clinicians' conflict resolution skills. Methods: Sixty clinicians from local hospitals were randomized into an intervention group (n = 30), completing a 3-hour conflict resolution training session, and a control group (n = 30) without training. The training included facilitated practice with actors, coaching, and feedback. Evaluation of 60 participants' conflict resolution skills was done in videotaped simulations with actors portraying interprofessional colleagues. Global ratings and checklist items developed for assessing clinicians' performance mirrored steps in the conflict communication model. Results: The intervention group's performance exceeded the control group on global scores, 7.2 of 10 (SD = 1.6) versus 5.6 (SD = 1.5), p < .05, and checklist scores, 9.3 of 11 (SD = 2.9) versus 7.9 (SD = 1.5), p < .05. Two checklist items showed statistically significant differences: (1) subjects opened the dialogue on a neutral ground before jumping into conflict discussions (intervention: 97% and control: 73%, p < .05) and (2) subjects elicited the colleague's story before sharing their own story (intervention: 70% and control: 27%, p < .05). Conclusions: The pilot results suggest that a health care–specific approach to conflict resolution can be effectively taught through facilitated practice, coaching, and feedback. Abstract : Supplemental Digital Content is Available in the Text.